2017
DOI: 10.1021/acs.bioconjchem.7b00502
|View full text |Cite
|
Sign up to set email alerts
|

Toward Personalized Peptide-Based Cancer Nanovaccines: A Facile and Versatile Synthetic Approach

Abstract: Personalized cancer vaccines (PCVs) are receiving attention as an avenue for cancer immunotherapy. PCVs employ immunogenic peptide epitopes capable of stimulating the immune system to destroy cancer cells with great specificity. Challenges associated with effective delivery of these peptides include poor solubility of hydrophobic sequences, rapid clearance, and poor immunogenicity, among others. The incorporation of peptides into nanoparticles has the potential to overcome these challenges, but the broad range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 75 publications
0
43
0
Order By: Relevance
“…High levels of tumor-infiltrating T cells are associated with improved prognosis in many cancers, so it is expected that new-generation vaccines will induce effective Th1 and CD8 + CTL responses ( Fig. 1) [3,[16][17][18][19]. Efficient delivery of antigens and adjuvants to antigenpresenting cells (APCs) in lymphoid organs (peripheral lymph nodes), cytosolic delivery and cross-presentation (complexation with MHC I) of tumor-associated antigens (TAAs), and activation of DCs by appropriate stimulators are desired.…”
Section: Lymph Node-targeting Nanovaccinesmentioning
confidence: 99%
“…High levels of tumor-infiltrating T cells are associated with improved prognosis in many cancers, so it is expected that new-generation vaccines will induce effective Th1 and CD8 + CTL responses ( Fig. 1) [3,[16][17][18][19]. Efficient delivery of antigens and adjuvants to antigenpresenting cells (APCs) in lymphoid organs (peripheral lymph nodes), cytosolic delivery and cross-presentation (complexation with MHC I) of tumor-associated antigens (TAAs), and activation of DCs by appropriate stimulators are desired.…”
Section: Lymph Node-targeting Nanovaccinesmentioning
confidence: 99%
“…[107] The results demonstrated that the selfassembled spherical nanovaccines were poorly immunogenic and needed to be combined with an adjuvant CpG. For instance, personalized cancer vaccines were designed using amphiphilic hyperbranched polymer-peptide conjugates including melanoma antigen peptides, a hydrophobic peptide tyrosinaserelated protein 2 (TRP2) or a hydrophilic tumor-associated mucin 30 peptide (MUC30).…”
Section: Allergen Peptidesmentioning
confidence: 99%
“…The balanced response of DCs plays a critical role in effective cancer immunotherapy. Therefore, NP‐based delivery systems can be employed to elicit a particular response (Table ) …”
Section: Cancer Immunotherapy By Regulating Dendritic Cells With Non‐mentioning
confidence: 99%